Mapping the psychosocial and practical support needs of cancer patients in Western Australia - White, K.; D'abrew, N.; Katris, P.; O'Connor, Moira; Emery, L. (Blackwell Publishing Ltd, 2011)
Understanding the unmet needs of cancer patients is important for developing and refining services to address the identified gaps in cancer care. In order to describe the psychological and practical support needs of Western Australians with cancer, the Western Australian Cancer Registry was used to identify a sample of individuals with cancer. These individuals were then invited to complete the Supportive Care Needs Survey (SCNS-LF59) and a demographic questionnaire. Data from participants who completed and returned both questionnaires were analysed using descriptive statistics, chi-square tests and one-way anova. Of the 1770 participants identified and contacted, a total of 829 individuals (47% response) completed the SCNS-LF59 alone, and 786 (94.8%) completed both questionnaires. Overall, a substantial minority of Western Australian cancer patients reported unmet needs, primarily in the psychological and physical and daily living domains. Disease-specific needs were also identified for the five most common cancer groups in Australia; for example, prostate cancer patients had unmet needs relating to sexuality, and melanoma patients had unmet informational needs. Cancer services need to look at how best to tailor resources and interventions to meet these needs of specific cancer subpopulations.